What memory representation is acquired during nonword speech production learning? The influence of stimulus features and training modality on nonword encoding - Kimberly M. Meigh; Susan Shaiman; Connie A. Tompkins; Katherine Verdolini Abbott; Timothy Nokes-Malach (Cogent Psychology, 2018)
The purpose of this research was to investigate memory representations related to speech processing. Psycholinguistic and speech motor control theorists have hypothesized a variety of fundamental memory representations, such as syllables or phonemes, which may be learned during speech acquisition tasks. Yet, it remains unclear which fundamental representations are encoded and retrieved during learning and generalization tasks. Two experiments were conducted using a motor learning paradigm to investigate if representations for syllables and phonemes were acquired during a nonword repetition task. Additionally, different training modalities were implemented across studies to examine if training modality influenced memory encoding for nonword stimuli. Results suggest multiple representations may be acquired during training regardless of training modality; however, the underlying memory representations learned during training may be less abstract than current models hypothesize.